An investigation into the effect of ribosomal protein S15 phosphorylation on its intermolecular interactions by using phosphomimetic mutant. Issue 57 (25th June 2020) - Correddu, Danilo; Sharma, Nabangshu; Kaur, Simranjeet; Varnava, Kyriakos G.; Mbenza, Naasson M.; Sarojini, Vijayalekshmi; Leung, Ivanhoe K. H.
Abstract : An investigation using recombinant ribosomal proteins and synthetic peptide models was conducted to uncover the effect of the introduction of a negative charge at the C-terminal tail of ribosomal protein S15. Abstract : An investigation using recombinant ribosomal proteins and synthetic peptide models was conducted to uncover the effect of the introduction of a negative charge at the C-terminal tail of ribosomal protein S15. Our results help provide a chemical rationale towards understanding how G2019S LRRK2, a common clinical mutation, causes Parkinson's disease.